Barbados. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Barbados during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as food security, organic agriculture, agribusiness, sustainability, livestock, agrotourism, protected agriculture and food safety. Finally, technical support was provided in forage, good manufacturing practices, processing manual, inclusion of youth, small ruminant breeding, such as sheep, and in the control of citrus pests and diseases.